Death in Archaeology: Crossed Views / Oppsed Positions - Alejandra Sánchez Polo (El Futuro del Pasado, 2010)
Death, necropolis and the objects buried togetherwith the deceased, represented an attraction to the first archaeologists that dug up –with little but an undoubted scientific interest– these valuabletreasures in countless sites for two centuries. After words, this antiquarist vision of Archaeology has been abandoned to adopt other reference frames that did not take precedence over the object itselfbut also to the societywhichmanufactured it. In the present communication, Iwill dealwith theoretical positions that mark a historical milestone in the historiography along the XX century, taking samples fromexcavated sites, putting special emphasis on howscientific interest accent different aspects in eachperiod. Finally, Iwill achieve a notice about themost vanguardist frameworkswhich explore the rational horizons of past people.